Patient’s experience at the intensive care unit in tertiary hospital, Malaysia - Mohamed Ariffin, Suzilawati; Pinyokham, Nitaya; Tachaudomdach, Chiraporn (2017)
INTRODUCTION AND OBJECTIVES The critically ill needs advanced support to prevent complications and survive. Critical care nurses have a pivotal role in identifying traumatic experiences of their patients. Patients may experience either pleasant or unpleasant memories during their stay at ICU. Unpleasant experiences can affect patients and later lead to negative consequences. This study aimed to explore the experiences of stay at the ICU among ICU survivors.